Predictive utility of the C-reactive protein to albumin ratio in early allograft dysfunction in living donor liver transplantation: A retrospective observational cohort study - Park, Jaesik (PLoS One, 2019)
BACKGROUND: This study was performed to determine the association between the ratio of C-reactive protein to albumin (CRP/ALB) and the risk of early allograft dysfunction (EAD) in patients undergoing living donor liver transplantation (LDLT). PATIENTS AND METHODS: A total of 588 adult patients undergoing LDLT were retrospectively investigated, after 22 were excluded because of signs of overt infection or history of ALB infusion. The study population was classified into high and low CRP/ALB ratio groups according to EAD. All laboratory variables, including CRP and ALB, had been collected on the day before surgery. A percentage value for the CRP/ALB ratio (%) was calculated as CRP/ALB × 100. RESULTS: After LDLT, 83 patients (14.1%) suffered EAD occurrence. A higher CRP/ALB ratio was independently associated with risk of EAD, Model for End-stage Liver Disease score, fresh frozen plasma transfusion, and donor age. Based on a cutoff CRP/ALB ratio (i.e., > 20%), the probability of EAD was significantly (2-fold) higher in the high versus low CRP/ALB group. The predictive utility of CRP/ALB ratio for EAD was greater than those of other inflammatory markers. In addition, patients with a high CRP/ALB ratio had poorer survival than those with a low CRP/ALB ratio during the follow-up period. CONCLUSIONS: The easily calculated CRP/ALB ratio may allow estimation of the risk of EAD after LDLT and can provide additional information that may facilitate the estimation of a patient’s overall condition.